Biphasic Synthesis of Large‐Pore and Well‐Dispersed Benzene Bridged Mesoporous Organosilica Nanoparticles for Intracellular Protein Delivery. Issue 23 (4th February 2015) - Yang, Yannan; Niu, Yuting; Zhang, Jun; Meka, Anand Kumar; Zhang, Hongwei; Xu, Chun; Lin, Chun Xiang Cynthia; Yu, Meihua; Yu, Chengzhong
<x xml:space="preserve">Abstract</x> Large pore (4.6–7.6 nm) and well‐dispersed benzene bridged mesoporous organosilica nanoparticles with uniform particle size of ≈50 nm are prepared via a biphasic approach. They can be directly used as nanocarriers without surface modification for the intracellular delivery of therapeutic proteins.